Unravelling the bioprospects of mycoendophytes residing in Withania somnifera for productive pharmaceutical applications. (October 2021) - Varghese, Sherin; Akshaya, C.S.; Jisha, M.S.
Abstract: Microorganisms are narrowly exploited, inspite of their limitless potential in synthesizing bioactive compounds having therapeutic applications. In our continuous search for novel, effective and safe therapeutics, endophytic fungi have proved their role as an alternative and reliable source of medically important bioactive compounds which have diverse medicinal applications. Medicinal herbs are generally considered as a storehouse of endophytes. Mycoendophytes residing in medicinal plants are renowned for their potentiality to synthesize active secondary metabolites such as alkaloids, aliphatic compounds, phenylpropanoids, polyketides, peptides, terpenoids etc. having medicinal value. They are also credited for their diverse biological activities including antibacterial, cytotoxic and antioxidant properties. They can be applied successfully in treating diseases like cancer, cardiovascular diseases and many other deadly ailments. With the emergence of various life threatening diseases, an imperative exploration of novel bioactive natural products produced by mycoendophytes residing in medicinal plants for developing potent drugs seems to appear as a promising approach. This review article aims to provide a detailed account on mycoendophytes residing in Withania somnifera, a medicinal herb renowned for its high pharmacological action. Various bioactive secondary metabolites produced by these mycoendophytes having therapeutic applications in various diseases with reference to their structure-activity studies are being discussed in this article. Highlights: Mycoendophytes are considered as an elective source for novel compounds with therapeutic applications. Withania somnifera, an esteemed medicinal plant in Ayurveda, embraces a plethora of mycoendophytes. Mycoendophytes associated with Withania somnifera produces various bioactive compounds with biopharmaceutical effects. Hence, these bioactive compounds may be exploited for the development of effective pharmaceutical products.